Zum Verschwinden des Vertrauens in Theorien der Rationalität und in der Praxis des Krieges - Stekeler, Pirmin (Philosophische Rundschau, 2022)
Free cooperation as well as peace are impossible without trust as an unconditioned prerequisite. Therefore, both formal theories of decisions under insecure conditions, as well as any (system-theoretical) social- or minimal moral theory of purely rational pursuit of well-understood self-interest (Nash, Becker, Luhmann; Lewis, Axelrod, Gauthier) founder on the fact that they only model the thinking of an entity from the animal kingdom in terms of cognition. Such animals are not even capable of practical reason in the sense of Kant's higher order principle of morals or cooperation regarding free joint willing. In order to achieve this, we have to bear the risk of trust while acting freely, as highlighted by both Socrates and Christianity. We may fight back only in the case of an attack on peace, as can be gleaned from what we will call the 'Ukraine-dilemma'. One advancement of the modern world consists in the fact that war is (at least in principle and unlike during the times of Clausewitz) not tolerated as a means of politics and leads to the exclusion from free cooperation.Robert Axelrod: The Evolution of Cooperation. New York 1984: Basic Books. X, 241 S. Dt.: Die Evolution der Kooperation. München 1988: Oldenbourg. X, 235 S. - Gary S. Becker: Der ökonomische Ansatz zur Erklärung menschlichen Verhaltens. Tübingen 1993: Mohr Siebeck. VI, 351 S. - Nuel Belnap, Michael Perloff, Ming Xu: Facing the Future. Agents and Choicesin our Indeterminist World. Oxford Univ. Pr. 2002. 520 S. - Carl Clausewitz: Vom Kriege, hg. v. W. Pickert und W. Ritter von Schramm. Reinbek 1963: rororo. 288 S. - David Gauthier: Morals by Agreement. Oxford 1986: Clarendon. VI, 367 S. - Gebhard Kirchgässner: Homo Oeconomicus. Das ökonomische Modell individuellen Handelns und seine Anwendung in den Wirtschafts- und Sozialwissenschaften. Tübingen 1991, 2008: Mohr Siebeck. 427 S. - Jakub Kloc-Konkołowicz: Anerkennung als Verpflichtung. Würzburg 2015: Königshausen & Neumann. XIV, 194 S. - David Lewis: Conventions. A Philosophical Study. Oxford 1969: Oxford Univ. Pr.